Counter-rotating type tidal stream power unit: Excellent performance verified at offshore test. Issue 5 (March 2019) - Samura, Isao; Kuwano, Kazuo; Kawashima, Ryunosuke; Oda, Taizo; Imakyurei, Takumi; Inoue, Hideyuki; Tokunaga, Yuuichiro; Kanemoto, Toshiaki; Miyagawa, Kazuyoshi; Miwa, Toshihiko; Yamanokuchi, Hiroshi
Abstract: A counter-rotating type tidal stream power unit, composed of tandem propellers and a peculiar generator with double rotatable armatures, was provided for verification tests at offshore. The front propeller with diameter of 1 m has three blades, and the rear propeller with diameter of 0.95 m has five blades. The blade profiles were optimized with the blade element-momentum theory and CFD, and then covered with CFRP. The front and the rear propellers connect to inner and outer armatures in a synchronous type generator with net output 1.5 kW, whose efficiency was improved by heat pipes and the modification of the armature profiles. The shafts are equipped with mechanical seals to protect electric circuits from seawater. A rotational speed control system was also prepared not only to adjust the output but also to overcome the static friction torque due to bearings, slip rings and mechanical seals while starting-up. The power unit takes the maximum output with excellent efficiency at the relative tip speed ratio specified in the unit design. The unit can start-up after maintenance works and the output can be adjusted smoothly in the stream.